Evaluation of Different Vitamin Concentrations on Grow-Finish Pig Growth and Carcass Characteristics - L. Del Tuffo; S. S. Dritz; M. D. Tokach; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2018)
Vitamins are generally added to swine diets in concentrations well above their requirement estimates to provide a generous margin of safety. However, with the increase in vitamin prices in 2017, there was a need to re-evaluate suggested vitamin additions. Therefore, the objective of this study was to compare two premixes with different vitamin concentrations on growth performance and carcass characteristics of grow-finish pigs reared in a commercial environment. A total of 1,188 pigs (PIC 359 × 1050; initially 35.5 lb) were used in a randomized complete block design with 27 pigs per pen and 22 pens per treatment. The experimental diets were corn-soybean meal-DDGS-based and were fed in 5 phases from approximately 35 to 60, 60 to 110, 110 to 165, 165 to 220, and 220 to 280 lb. There were two dietary treatments based on different vitamin concentrations. The first was the Kansas State University recommended vitamin premix up to December 2017. It contained 1,600,000 IU vitamin A; 400,000 IU vitamin D, 8,000 mg vitamin E; 800 mg vitamin K; 7 mg vitamin B12; 15,000 mg niacin; 5,000 mg pantothenic acid; and 1,500 mg riboflavin. The second was the K-State recommended vitamin premix since January 2018. It contained: 750,000 IU vitamin A; 300,000 IU vitamin D; 8,000 mg vitamin E; 600 mg vitamin K; 6 mg vitamin B12; 9,000 mg niacin; 5,000 mg pantothenic acid; and 1,500 mg riboflavin. Overall (d 0 to 138), there was no evidence for differences in average daily gain (ADG), average daily feed intake (ADFI), or feed efficiency (F/G). Also, no evidence for differences was observed for final weight, hot carcass weight or any other carcass characteristic. In conclusion, the new K-State 2018 recommended vitamin premix concentrations provided similar growth performance as the 2017 recommendations, while not influencing carcass traits in grow-finish pigs.
Keywords: Finishing pigs; growth performance; vitamins